Histochemical Methods for Identification of Zinc ions in Pancreatic Islets, Prostate and in Salivary Glands - Kikimbaeva, A.A.; Kohnert, K.-D.; Meyramov, G.G.; Kartbaeva, G.T.; Shaybek, A.S.; Gagolina, S.V.; Mindubaeva, F.A.; Tulieva, A.M.; Zhuzbaeva, G.O.; Abdraimova, A.G.; et al. (Fundamental and Experimental Biology, 2016)
Authors have used two histochemical methods: 8PTSQ, a high specific fluorescent and Dithizon method for identification of Zinc in the frozen and paraffin sections of tissues of pancreas as in tissues of prostate and salivary glands. It was showed that 10–15 min past one injection to animals of diabetogenic chelators (DC) result accompanied by binding of Zn ions and by negative reaction for Zn in B-cells determined absence of free Zn ions for staining. In the contrary, 5–7 days past injection of DC reaction for Zn in B-cells was nega-tive as result of destruction of cells and of almost complete disappearing of Zn ions from B-cells. Analogical negative reaction for Zn ions there are in B-cells past elimination of Zn by Glibenclamide. Meanwhile administration of Glibenclamide accompanied by elimination of Zinc ions from B-cells only, not from cells of prostate and from salivary glands. It was demonstrated that Dithizon method is more preferable for more detail investigation of location of Zinc in various parts of B-cells. The advantage of 8PTSQ fluorescent method determined by more high sensitivity in compared with Dithizon method. It is established that lifetime coloring of pancreatic B-cells of islets, of trailer part of epithelium cells of Prostate and salivary glands after administration of Ditizon to animals allows to study in detail in them location of Zinc using microscopy in the dark field.